K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 2

3/4-(-1/2)+(-5/12)

=3/4+1/2-5/12

=9/12+6/12-5/12

=9+6-5/12

=10/12

=5/6

\(\dfrac{3}{4}-\left(-\dfrac{1}{2}\right)+\left(-\dfrac{5}{12}\right)\)
\(=\dfrac{3}{4}+\dfrac{1}{2}-\dfrac{5}{12}\)
\(=\dfrac{9}{12}+\dfrac{6}{12}-\dfrac{5}{12}\)
\(=\dfrac{10}{12}=\dfrac{5}{6}\)

19 tháng 4 2019

a) \(3^4.\left(-4\right)^2=3^4.4^2=3^4.2^4=\left(3.2\right)^4=6^4\)

b) \(=1\frac{3}{5}+\left(6+\frac{5}{11}-4-\frac{5}{11}\right).\frac{1}{5}=1+\frac{3}{5}+2.\frac{1}{5}=2\)

c)\(=4.\left(0,75-0,25\right)=4.0,5=2\)

d) \(=\frac{\frac{1}{3}+\frac{3}{4}+\frac{3}{2}}{\frac{1.4}{3.4}+\frac{3.3}{4.3}+\frac{3.6}{2.6}}=\frac{\frac{1}{3}+\frac{3}{4}+\frac{3}{2}}{\frac{1}{3}+\frac{3}{4}+\frac{3}{2}}=1\)

Bài 1:

a) Ta có: \(\frac{5}{6}-\frac{2}{3}+\frac{1}{4}\)

\(=\frac{10}{12}-\frac{8}{12}+\frac{3}{12}\)

\(=\frac{2+3}{12}=\frac{5}{12}\)

b) Ta có: \(1\frac{11}{12}-\frac{5}{12}\cdot\left(\frac{4}{5}-\frac{1}{10}\right):\frac{-5}{12}\)

\(=\frac{23}{12}-\frac{5}{12}\cdot\left(\frac{8}{10}-\frac{1}{10}\right)\cdot\frac{-12}{5}\)

\(=\frac{23}{12}-\frac{5}{12}\cdot\frac{7}{10}\cdot\frac{-12}{5}\)

\(=\frac{23}{12}-\frac{-7}{10}\)

\(=\frac{115}{60}+\frac{42}{60}=\frac{157}{60}\)

Bài 2:

a) Ta có: \(\frac{1}{2}\cdot x-\frac{2}{5}=\frac{1}{5}\)

\(\Leftrightarrow\frac{1}{2}\cdot x=\frac{1}{5}+\frac{2}{5}=\frac{3}{5}\)

\(\Leftrightarrow x=\frac{3}{5}:\frac{1}{2}=\frac{3}{5}\cdot2=\frac{6}{5}\)

Vậy: \(x=\frac{6}{5}\)

b) Ta có: \(\left(1-2x\right)\cdot\frac{4}{3}=\left(-2\right)^3\)

\(\Leftrightarrow\left(1-2x\right)\cdot\frac{4}{3}=-8\)

\(\Leftrightarrow1-2x=-8:\frac{4}{3}=-8\cdot\frac{3}{4}=-6\)

\(\Leftrightarrow-2x=-6-1=-7\)

hay \(x=\frac{7}{2}\)

Vậy: \(x=\frac{7}{2}\)

14 tháng 8 2020

lớp 9 đấy!

30 tháng 4 2019

\(\left(\frac{3}{8}+-\frac{3}{4}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)

\(=\left(\frac{9}{24}+-\frac{18}{24}+\frac{14}{24}\right):\frac{5}{6}+\frac{1}{2}\)

\(=\frac{5}{24}:\frac{5}{6}+\frac{1}{2}\)

\(=\frac{5}{24}.\frac{6}{5}+\frac{1}{2}\)

\(=\frac{1}{4}+\frac{1}{2}\)

\(=\frac{1}{4}+\frac{2}{4}\)

\(=\frac{3}{4}\)

30 tháng 4 2019

\(\frac{1}{2}+\frac{3}{4}-\left(\frac{3}{4}-\frac{4}{5}\right)\)

\(=\frac{1}{2}+\frac{3}{4}-\left(\frac{15}{20}-\frac{16}{20}\right)\)

\(=\frac{1}{2}+\frac{3}{4}-\frac{-1}{20}\)

\(=\frac{10}{20}+\frac{15}{20}-\frac{-1}{20}\)

\(=\frac{25}{20}-\frac{-1}{20}\)

\(=\frac{26}{20}\)

\(=\frac{13}{10}\)

Bài 6:

a: \(x=-\dfrac{2}{3}-\dfrac{1}{7}=\dfrac{-14-3}{21}=\dfrac{-17}{21}\)

d: \(x=\dfrac{9}{10}\cdot\dfrac{-5}{9}=\dfrac{-1}{2}\)

e: \(\Leftrightarrow x\cdot\dfrac{1}{3}=\dfrac{14}{21}-\dfrac{3}{21}=\dfrac{11}{21}\)

=>x=11/7

26 tháng 7 2017

a, \(4\times\left(-\dfrac{1}{2}\right)^3-2\times\left(-\dfrac{1}{2}\right)^2+3\times\left(-\dfrac{1}{2}\right)+1\)

\(=\left(-\dfrac{1}{2}\right)\left[\left(4\times-\dfrac{1}{2}\right)-\left(2\times-\dfrac{1}{2}\right)+3\right]+1\)

\(=\left(-\dfrac{1}{2}\right)\left(-2+1+3\right)+1\)

\(=\left(-\dfrac{1}{2}\right)2+1\)

\(=-1+1\)

\(=0\)

@Trịnh Thị Thảo Nhi

29 tháng 4 2018

a, 4×(−12)3−2×(−12)2+3×(−12)+14×(−12)3−2×(−12)2+3×(−12)+1

=(−12)[(4×−12)−(2×−12)+3]+1=(−12)[(4×−12)−(2×−12)+3]+1

=(−12)(−2+1+3)+1=(−12)(−2+1+3)+1

=(−12)2+1=(−12)2+1

=−1+1=−1+1

=0=0

25 tháng 4 2017

\(-2\dfrac{1}{4}.\)\(\left(3\dfrac{5}{12}-1\dfrac{2}{9}\right)\)

=\(\dfrac{-9}{4}\).\(\left(\dfrac{41}{12}-\dfrac{11}{9}\right)\)

=\(\dfrac{-9}{4}.\dfrac{41}{12}-\dfrac{-9}{4}.\dfrac{11}{9}\)

=\(\dfrac{-123}{16}-\dfrac{-11}{4}\)

=\(\dfrac{-123}{16}-\dfrac{-44}{16}\)

=\(\dfrac{-79}{16}\)

25 tháng 4 2017

\(\left(-25\%+0,75+\dfrac{7}{12}\right)\div\left(-2\dfrac{1}{8}\right)\)

=\(\left(\dfrac{-1}{4}+\dfrac{3}{4}+\dfrac{7}{12}\right)\div\left(\dfrac{-17}{8}\right)\)

=\(\left(\dfrac{-3}{12}+\dfrac{9}{12}+\dfrac{7}{12}\right).\dfrac{-8}{17}\)

=\(\dfrac{13}{12}.\dfrac{-8}{17}=\dfrac{-26}{51}\)

24 tháng 3 2019

a) \(\frac{14}{21}+1-\left|\frac{1}{3}-1\right|\)

\(=\frac{2}{3}+1-\frac{2}{3}\)

\(=1+\left(\frac{2}{3}-\frac{1}{3}\right)\)

\(=1\)

b) \(\frac{1}{3}-\left|\frac{-1}{4}+\frac{5}{6}\right|-\left|\frac{-7}{12}\right|\)

\(=\frac{1}{3}-\frac{7}{12}-\frac{7}{12}\)

\(=-\frac{5}{6}\)

24 tháng 3 2019

Các câu khác làm tương tự thôi :))